Systematics of lionfishes (Scorpaenidae: Pteroini) using molecular and morphological data - Chou, Tak-Kei; Liu, Min-Yun; Liao, Te-Yu (Frontiers in Marine Science, 2023)
Lionfishes (Tribe Pteroini) are eye-catching due to distinct elongated fins and warning coloration. The monophyly of the Pteroini is supported by recent phylogenetic analyses. However, the interrelationships of inter- and intra-genera of the Pteroini are contentious. In this study, 5335 bps of two mitochondrial and five nuclear genes were sequenced to reconstruct the phylogeny of lionfishes. Our analyses showed Dendrochirus and Pterois were both not monophyletic and divided into Dendrochirus I, II and III clades (D. I, II, III) and Pterois I and II clades (Pt. I, II), respectively. Pt. I was sister to the Pt. II+D. I clade. D. II was the sister group of the Ebosia+Parapterois clade. The D. III clade was at the base of the Pteroini followed by the genus Brachypterois. Morphologically, we provided combinations of characters to distinguish all clades. According to the molecular and morphological data, we propose a revised taxonomy of the Pteroini. D. I and Pt. I hold the generic name of Dendrochirus and Pterois, respectively. Neochirus gen. n. is proposed as a new genus for the D. II clade. The genera Pteropterus Swainson 1839 and Nemapterois Fowler 1938 are revalidated for Pt. II and D. III, respectively.